Organic-inorganic P (g42T-T) / GaON (Sn) pn junction deep ultraviolet photoelectric detector and preparation method thereof
By synthesizing organic-inorganic P(g42T-T)/GaON(Sn)pn junction structure on quartz substrate, the problems of slow response speed and material defects of traditional optoelectronic devices are solved, and deep ultraviolet photoelectricity with high sensitivity and fast response are achieved Detection device, suitable for detection of extremely weak ultraviolet signals.
Patent Information
- Application Number
- CN202411449520.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional optoelectronic devices have slow response speed, and the materials have problems such as large lattice mismatch and many interface defects.
Using an organic-inorganic P(g42T-T)/GaON(Sn) pn junction structure, the GaON(Sn) film and P(g42T-T) film layer were synthesized on a quartz substrate, and the Ag nanowire film layer was spin-coated. A built-in electric field is formed to efficiently separate photogenerated carriers.
It realizes a deep ultraviolet photodetection device with fast response speed and high sensitivity under 0V bias voltage. It is suitable for monitoring daily blind ultraviolet signals and has a broad range of extremely weak deep ultraviolet signals detection such as corona, arc, and electric spark. Application prospects.
Smart Images

Figure CN119451370A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectric detection devices, and in particular relates to an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photoelectric detection device and a preparation method thereof. Background Art
[0002] Gallium oxide is a new type of ultra-wide bandgap oxide semiconductor material with a bandgap of 4.7 to 5.3 eV, which is in the solar-blind region (200 to 280 nm). It also has extremely high chemical and thermal stability and is a natural solar-blind detection material. However, oxygen vacancies are inevitably introduced during the preparation of gallium oxide thin films, affecting their photoelectric properties.
[0003] At present, GaON solar-blind detection devices based on MSM structures generally have limitations such as slow response speed and the need for external bias voltage. In contrast, heterojunction photodetection devices exhibit faster response speed and self-powered characteristics. In addition, traditional heterojunction detection devices have problems such as large lattice mismatch and many interface defects. Summary of the invention
[0004] In order to solve the problems of slow response speed and material defects of traditional photoelectric devices, the present invention provides an organic-inorganic P(g42T-T) / GaON(Sn)pn junction deep ultraviolet photoelectric detection device with high sensitivity, fast response speed, strong detection capability and self-power supply and a preparation method thereof. The device has great application prospects in the fields of corona, arc and extremely weak ultraviolet detection.
[0005] In order to achieve the above technical purpose, the present invention adopts the following technical solutions:
[0006] An organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device comprises a quartz substrate, a GaON(Sn) film, a P(g42T-T) film layer, an Ag nanowire / Ti / Au electrode, and a Ti / Au electrode.
[0007] Furthermore, in the photodetector device, the GaON (Sn) thin film is located on a quartz substrate, and the P (g42T-T) thin film
[0008] The film layer is located above one side of the GaON (Sn) film, an Ag nanowire film layer is spin-coated on the P (g42T-T) film layer, and the first test electrode Ti / Au film is evaporated on it, and the second test electrode Ti / Au film is located above the other side of the GaON (Sn) film. The contact surface of the P (g42T-T) film layer and the GaON (Sn) film forms an organic-inorganic P (g42T-T) / GaON (Sn) pn junction, forming a built-in electric field to efficiently separate photogenerated carriers.
[0009] Furthermore, the mass percentage of Sn in the GaON(Sn) film is 3-5%.
[0010] A method for preparing the organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device as described above, the steps of which are as follows:
[0011] Step 1: Pre-treat the quartz substrate by ultrasonically cleaning it with acetone, anhydrous ethanol and deionized water for 5 to 10 minutes in sequence, and then drying it with high-purity nitrogen gas;
[0012] Step 2: using plasma enhanced chemical vapor deposition (PECVD) technology to prepare an n-type GaON (Sn) thin film on a quartz substrate at a certain growth temperature and time;
[0013] Step 3: Take an appropriate amount of P(g42T-T) powder and chlorobenzene and add them into a beaker to evenly dissolve them to obtain a P(g42T-T) solution for standby use;
[0014] Step 4: Take an appropriate amount of Ag nanowire powder and anhydrous ethanol and add them into a beaker to mix them evenly to obtain a Ag nanowire mixed solution for standby use;
[0015] Step 5: The P(g42T-T) solution obtained in step 3 is evenly distributed on one side of the GaON(Sn) film by spin coating, and dried on a drying platform at 100° C. for 5-10 minutes to form a p-type P(g42T-T) thin film layer, thereby obtaining an organic-inorganic P(g42T-T) / GaON(Sn) pn junction on the quartz substrate;
[0016] Step 6: Spin-coat the Ag nanowire mixture obtained in step 4 evenly on the P(g42T-T) film layer, and dry at 100° C. for 5-10 min to form an Ag nanowire film layer;
[0017] Step seven: Evaporate a square Ti / Au film on the Ag nanowire film layer and the GaON (Sn) film as a first test electrode and a second test electrode, respectively.
[0018] Preferably, the purity of the raw material metal gallium particles for preparing the GaON (Sn) film in step 2 is 99.999%, and the purity of the metal tin powder is 99.999%. The metal gallium is first heated to 40° C. to form liquid gallium, and an appropriate amount of tin powder is added to the liquid gallium until it is completely dissolved to form a gallium-tin alloy. Finally, the quartz substrate and the gallium-tin alloy are placed at both ends of an alumina crucible boat, and heated to react at an oxygen gas flow rate range of 1 to 10 sccm, a nitrogen gas flow rate range of 10 to 100 sccm, and an argon gas flow rate range of 1 to 100 sccm.
[0019] More preferably, the growth temperature in step 2 is 800-1000° C., the growth time is 30-120 min, and the RF power is 50-200W.
[0020] Preferably, the purity of the P(g42T-T) powder in step three is 99.999%, the concentration of the P(g42T-T) solution is 0.1-10 mg / mL, and it is dispersed by an ultrasonic cleaning machine with an ultrasonic power of 100-200 W and an ultrasonic time of 10-20 min.
[0021] Preferably, in the spin coating method described in step 5, the heating temperature of the spin coating is 50-150° C., the heating rate is 1-5° C. / s; the spin coating speed is 1000-3000 rpm, the acceleration is 100-1000 rpm / s; and the spin coating time is 30-90s.
[0022] Preferably, in step seven, the first test electrode and the second test electrode are both made of metal electrode materials selected from one or more of Au, Ag, Ti, Ni and Al, and the thickness of the metal electrode layer is 50-200 nm.
[0023] More preferably, the metal electrode is obtained by one method or a combination of multiple methods selected from magnetron sputtering, thermal evaporation and electron beam evaporation.
[0024] Advantages and beneficial effects of the present invention:
[0025] 1. The deep ultraviolet photodetector device of the present invention synthesizes an organic-inorganic P(g42T-T) / GaON(Sn) pn junction on a quartz substrate. The device operates in a self-powered mode and has a faster response speed and higher sensitivity under a 0V bias. It is an excellent device for monitoring solar-blind ultraviolet signals.
[0026] 2. The deep ultraviolet photodetector device of the present invention, by introducing N with a high p-orbital level into Ga2O3 to form a GaON nanomesh, can effectively shield the impurity level associated with oxygen vacancies, reduce the impact of oxygen vacancy-related defects, and improve the performance of the material in deep ultraviolet light detection.
[0027] 3. Compared with inorganic materials, organic materials are not restricted by lattice mismatch and have simple preparation methods, which helps to further improve the photoelectric performance of heterojunction devices. Among them, P(g42T-T) is a p-type organic semiconductor material. P(g42T-T) material has high hole mobility and high solar-blind light transmittance. It can form an organic-inorganic pn junction structure with n-type tin-doped GaON film, forming a built-in electric field and efficiently separating photogenerated carriers, making it an ideal hole transport material in photodetection devices.
[0028] 4. The deep ultraviolet photoelectric detection device preparation technology involved in the present invention has excellent performance stability due to its high process controllability and simple operation, and has broad application prospects in the field of extremely weak deep ultraviolet signal detection such as corona, arc, and spark. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0030] Figure 1 It is a schematic structural diagram of an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device prepared by the method of the present invention;
[0031] Figure 2 It curves of the organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device prepared by the method of the present invention at 0V bias voltage 254nm and different light intensities;
[0032] Figure 3 The organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device prepared by the method of the present invention has a 0V bias voltage and a 500μW / cm 2 Response speed under light intensity;
[0033] Figure 4 The organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device prepared by the method of the present invention has a bias voltage of 0V and a light intensity of 1500μW / cm 2 It curve under 254nm light. DETAILED DESCRIPTION
[0034] In order to deepen the understanding of the present invention, the contents of the present invention will be explained in detail and clearly in conjunction with the accompanying drawings.
[0035] Example 1
[0036] A method for preparing an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device, the steps are as follows:
[0037] Step 1: Pre-treat the quartz substrate by ultrasonically cleaning it with acetone, anhydrous ethanol and deionized water for 5 minutes in sequence, and then drying it with high-purity nitrogen gas;
[0038] Step 2: Prepare n-type GaON (Sn) thin film on a quartz substrate by plasma enhanced chemical vapor deposition (PECVD) technology; wherein the purity of the metal gallium particles is 99.999%, and the purity of the metal tin powder is 99.999%; the oxygen gas flow rate range is 5sccm, the nitrogen gas flow rate range is 20sccm, and the argon gas flow rate range is 50sccm; the growth temperature is 800°C, the growth time is 30min, and the RF power is 50W;
[0039] Step 3: Take an appropriate amount of P(g42T-T) powder and chlorobenzene and add them to a beaker to uniformly dissolve them to obtain a P(g42T-T) solution for standby use; wherein the purity of the P(g42T-T) powder is 99.999%, the concentration of the P(g42T-T) solution is 0.5 mg / mL, and it is dispersed by an ultrasonic cleaning machine, the ultrasonic power is 100 W, and the ultrasonic time is 15 min;
[0040] Step 4: Take an appropriate amount of Ag nanowire powder and anhydrous ethanol and add them into a beaker to mix them evenly to obtain a Ag nanowire mixed solution for standby use;
[0041] Step 5: The P(g42T-T) solution obtained in step 3 is evenly distributed on one side of the GaON(Sn) film by spin coating, and dried on a drying platform at 100°C for 5 minutes to form a p-type P(g42T-T) thin film layer, thereby obtaining an organic-inorganic P(g42T-T) / GaON(Sn) pn junction on the quartz substrate; wherein the heating temperature of the spin coating is 50°C, the heating rate is 3°C / s; the spin coating speed is 1000rpm, the acceleration is 1000rpm / s; and the spin coating time is 30s;
[0042] Step 6: evenly spin-coat the Ag nanowire mixture obtained in step 4 on the P(g42T-T) thin film layer, and dry at 100° C. for 5 min to form an Ag nanowire thin film layer;
[0043] Step 7: Evaporating a square Ti / Au film on the Ag nanowire film layer and the GaON (Sn) film as the first test electrode and the second test electrode, respectively. The first test electrode and the second test electrode are both metal electrode materials selected from one or more of Au, Ag, Ti, Ni and Al, and the thickness of the metal electrode layer is 100 nm. The metal electrode is obtained by one method or a combination of multiple methods selected from magnetron sputtering, thermal evaporation and electron beam evaporation.
[0044] Through the above experimental process, an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device can be prepared, such as Figure 1As shown, it includes a quartz substrate, a GaON (Sn) film, a P (g42T-T) film layer, an Ag nanowire / Ti / Au electrode, and a Ti / Au electrode in sequence. The GaON (Sn) film is located on the quartz substrate, the P (g42T-T) film layer is located on one side of the GaON (Sn) film, the Ag nanowire film layer is spin-coated on the P (g42T-T) film layer, and the first test electrode Ti / Au film is evaporated on the top, and the second test electrode Ti / Au film is located on the other side of the GaON (Sn) film. The contact surface of the P (g42T-T) film layer and the GaON (Sn) film forms an organic-inorganic P (g42T-T) / GaON (Sn) pn junction, forming a built-in electric field, and efficiently separating photogenerated carriers.
[0045] The photoelectric performance of the organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device obtained in the above steps was tested. The results showed that the device can operate under a bias voltage of 0V and has the characteristic of being self-powered. Figure 2 The It curves at 0V bias 254nm and different light intensities are given. It can be seen from the figure that at 50, 100, 200, 400, 600, 800, 1000 and 1500μW / cm 2 Under 254nm deep ultraviolet light irradiation, a stable It cycle curve can be obtained. Figure 2 The inset shows that the photocurrent obtained under different light intensities varies linearly. Figure 3 0V bias and 500μW / cm 2 The response speed diagram under light intensity shows that the device response time is 0.026 / 0.042s, which is an extremely fast response speed. Figure 4 The results are given at 0V bias and light intensity of 1500μW / cm 2 The It curve was measured by turning the light on and off continuously under 254nm light. In the dark, the dark current of the detector is 0.104μA. When the light intensity is 1500μW / cm 2 After irradiation with 254nm deep ultraviolet light, the current rapidly increased to 33.50μA, and the light-dark ratio I photo / I dark The sensitivity reaches 322. In summary, the device has fast response speed and high sensitivity, and has broad application prospects in the detection of extremely weak deep ultraviolet signals such as corona, arc, and spark.
[0046] Example 2
[0047] A method for preparing an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device, the steps are as follows:
[0048] Step 1: Pre-treat the quartz substrate by ultrasonically cleaning it with acetone, anhydrous ethanol and deionized water for 10 minutes in sequence, and then drying it with high-purity nitrogen gas;
[0049] Step 2: Prepare n-type GaON (Sn) thin film on a quartz substrate by plasma enhanced chemical vapor deposition (PECVD) technology; wherein the purity of the metal gallium particles is 99.999%, and the purity of the metal tin powder is 99.999%; the oxygen gas flow rate range is 10sccm, the nitrogen gas flow rate range is 100sccm, and the argon gas flow rate range is 100sccm; the growth temperature is 800°C, the growth time is 80min, and the RF power is 100W;
[0050] Step 3: Take an appropriate amount of P(g42T-T) powder and chlorobenzene and add them to a beaker to uniformly dissolve them to obtain a P(g42T-T) solution for standby use; wherein the purity of the P(g42T-T) powder is 99.999%, the concentration of the P(g42T-T) solution is 10 mg / mL, and it is dispersed by an ultrasonic cleaning machine, the ultrasonic power is 200 W, and the ultrasonic time is 20 min;
[0051] Step 4: Take an appropriate amount of Ag nanowire powder and anhydrous ethanol and add them into a beaker to mix them evenly to obtain a Ag nanowire mixed solution for standby use;
[0052] Step 5: The P(g42T-T) solution obtained in step 3 is evenly distributed on one side of the GaON(Sn) film by spin coating, and dried on a drying platform at 100°C for 10 minutes to form a p-type P(g42T-T) thin film layer, thereby obtaining an organic-inorganic P(g42T-T) / GaON(Sn) pn junction on the quartz substrate; wherein the heating temperature of the spin coating is 150°C, the heating rate is 5°C / s; the spin coating speed is 3000rpm, the acceleration is 500rpm / s; and the spin coating time is 60s;
[0053] Step 6: evenly spin-coat the Ag nanowire mixture obtained in step 4 on the P(g42T-T) thin film layer, and dry at 100° C. for 10 min to form an Ag nanowire thin film layer;
[0054] Step 7: Evaporating a square Ti / Au film on the Ag nanowire film layer and the GaON (Sn) film as the first test electrode and the second test electrode, respectively. The first test electrode and the second test electrode are both metal electrode materials selected from one or more of Au, Ag, Ti, Ni and Al, and the thickness of the metal electrode layer is 50 to 200 nm. The metal electrode is obtained by one or more methods selected from magnetron sputtering, thermal evaporation and electron beam evaporation.
[0055] The composition, structure and photoelectric performance of the obtained organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetection device are similar to those in Example 1.
[0056] Example 3
[0057] A method for preparing an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device, the steps are as follows:
[0058] Step 1: Pre-treat the quartz substrate by ultrasonically cleaning it with acetone, anhydrous ethanol and deionized water for 10 minutes in sequence, and then drying it with high-purity nitrogen gas;
[0059] Step 2: Prepare n-type GaON (Sn) thin film on a quartz substrate by plasma enhanced chemical vapor deposition (PECVD) technology; wherein the purity of the metal gallium particles is 99.999%, and the purity of the metal tin powder is 99.999%; the oxygen gas flow rate range is 1 to 10 sccm, the nitrogen gas flow rate range is 80 sccm, and the argon gas flow rate range is 60 sccm; the growth temperature is 900°C, the growth time is 90 minutes, and the radio frequency power is 150W;
[0060] Step 3: Take an appropriate amount of P(g42T-T) powder and chlorobenzene and add them to a beaker to uniformly dissolve them to obtain a P(g42T-T) solution for standby use; wherein the purity of the P(g42T-T) powder is 99.999%, the concentration of the P(g42T-T) solution is 6 mg / mL, and it is dispersed by an ultrasonic cleaning machine, the ultrasonic power is 180 W, and the ultrasonic time is 15 min;
[0061] Step 4: Take an appropriate amount of Ag nanowire powder and anhydrous ethanol and add them into a beaker to mix them evenly to obtain a Ag nanowire mixed solution for standby use;
[0062] Step 5: The P(g42T-T) solution obtained in step 3 is evenly distributed on one side of the GaON(Sn) film by spin coating, and dried on a drying platform at 100°C for 6 minutes to form a p-type P(g42T-T) thin film layer, thereby obtaining an organic-inorganic P(g42T-T) / GaON(Sn) pn junction on the quartz substrate; wherein the heating temperature of the spin coating is 120°C, the heating rate is 2°C / s; the spin coating speed is 1500rpm, the acceleration is 600rpm / s; and the spin coating time is 80s;
[0063] Step 6: evenly spin-coat the Ag nanowire mixture obtained in step 4 on the P(g42T-T) thin film layer, and dry at 100° C. for 6 min to form an Ag nanowire thin film layer;
[0064] Step 7: Evaporating a square Ti / Au film on the Ag nanowire film layer and the GaON (Sn) film as the first test electrode and the second test electrode, respectively. The first test electrode and the second test electrode are both metal electrode materials selected from one or more of Au, Ag, Ti, Ni and Al, and the thickness of the metal electrode layer is 50 to 200 nm. The metal electrode is obtained by one or more methods selected from magnetron sputtering, thermal evaporation and electron beam evaporation.
[0065] The composition, structure and photoelectric performance of the obtained organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetection device are similar to those in Example 1.
[0066] Obviously, the above embodiments are only examples for explaining the present invention and are not restrictive provisions for the implementation methods. For those skilled in the art, any equivalent replacement, improvement or adjustment made according to the methods and principles of the present invention, based on a full understanding of the above description, should be deemed to be included in the protection scope of the present invention. It is not necessary and unnecessary to list all possible implementation methods in detail and unlimitedly. Any obvious changes or adjustments derived therefrom should be deemed to be within the creative protection scope of the present invention.
Claims
1. An organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet photodetector device, characterized in that: The deep ultraviolet photodetector device comprises a quartz substrate, a GaON (Sn) film, a P (g42T-T) film layer, an Ag nanowire / Ti / Au electrode and a Ti / Au electrode.
2. The deep ultraviolet photodetector device according to claim 1, characterized in that: The GaON (Sn) film is located on the quartz substrate, the P (g42T-T) film layer is located above one side of the GaON (Sn) film, an Ag nanowire film layer is spin-coated on the P (g42T-T) film layer, and a first test electrode Ti / Au film is evaporated on top, and a second test electrode Ti / Au film is located above the other side of the GaON (Sn) film. An organic-inorganic P (g42T-T) / GaON (Sn) pn junction is formed at the contact surface between the P (g42T-T) film layer and the GaON (Sn) film, forming a built-in electric field to efficiently separate photogenerated carriers.
3. The deep ultraviolet photodetector device according to claim 2, characterized in that: The mass percentage of Sn in the GaON(Sn) film is 3-5%.
4. A method for preparing an organic-inorganic P(g42T-T) / GaON(Sn) pn junction deep ultraviolet detection device as claimed in any one of claims 1 to 3, characterized in that: The steps of the preparation method include the following: Step 1: Quartz substrate pretreatment: ultrasonically clean with acetone, anhydrous ethanol and deionized water for 5 to 10 minutes in sequence, and dry with high-purity nitrogen after cleaning; Step 2: using plasma enhanced chemical vapor deposition (PECVD) technology to prepare an n-type GaON (Sn) thin film on a quartz substrate at a certain growth temperature and time; Step 3: Take an appropriate amount of P(g42T-T) powder and chlorobenzene and add them into a beaker to evenly dissolve them to obtain a P(g42T-T) solution for standby use; Step 4: Take an appropriate amount of Ag nanowire powder and anhydrous ethanol and add them into a beaker to mix them evenly to obtain a Ag nanowire mixed solution for standby use; Step 5: The P(g42T-T) solution obtained in step 3 is evenly distributed on one side of the GaON(Sn) film by spin coating, and dried on a drying platform at 100° C. for 5-10 minutes to form a p-type P(g42T-T) thin film layer, thereby obtaining an organic-inorganic P(g42T-T) / GaON(Sn) pn junction on the quartz substrate; Step 6: Spin-coat the Ag nanowire mixture obtained in step 4 evenly on the P(g42T-T) film layer, and dry at 100° C. for 5-10 min to form an Ag nanowire film layer; Step seven: Evaporate a square Ti / Au film on the Ag nanowire film layer and the GaON (Sn) film as a first test electrode and a second test electrode, respectively.
5. The preparation method according to claim 4, characterized in that: In step 2, the purity of the raw material metal gallium particles for preparing the GaON (Sn) film is 99.999%, and the purity of the metal tin powder is 99.999%; first, the metal gallium is heated to 40° C. to form liquid gallium, and an appropriate amount of tin powder is added to the liquid gallium until it is completely dissolved to form a gallium-tin alloy. Finally, the quartz substrate and the gallium-tin alloy are placed at both ends of an alumina crucible boat, and heated to react at an oxygen gas flow rate range of 1 to 10 sccm, a nitrogen gas flow rate range of 10 to 100 sccm, and an argon gas flow rate range of 1 to 100 sccm.
6. The preparation method according to claim 5, characterized in that: The growth temperature in step 2 is 800-1000° C., the growth time is 30-120 min, and the radio frequency power is 50-200 W.
7. The preparation method according to claim 4, characterized in that: The purity of the P(g42T-T) powder in step 3 is 99.999%, the concentration of the P(g42T-T) solution is 0.1-10 mg / mL, and it is dispersed by an ultrasonic cleaning machine with an ultrasonic power of 100-200 W and an ultrasonic time of 10-20 min.
8. The preparation method according to claim 4, characterized in that: In the spin coating method described in step 5, the heating temperature of the spin coating is 50-150° C., the heating rate is 1-5° C. / s; the spin coating speed is 1000-3000 rpm, the acceleration is 100-1000 rpm / s; and the spin coating time is 30-90s.
9. The preparation method according to claim 4, characterized in that: In step seven, the first test electrode and the second test electrode are both made of metal electrode materials, the metal is selected from one or more of Au, Ag, Ti, Ni and Al, and the thickness of the metal electrode layer is 50 to 200 nm.
10. The preparation method according to claim 9, characterized in that: The metal electrode is obtained by one method or a combination of multiple methods selected from magnetron sputtering, thermal evaporation and electron beam evaporation.